Bearing capacity of aluminum alloy members under eccentric compression at elevated temperatures. (June 2018) - Zhu, Shaojun; Guo, Xiaonong; Liu, Xian; Jiang, Shouchao
Abstract: This paper investigates the elevated-temperature flexural-torsional buckling behavior of aluminum alloy members under eccentric compression by means of experimental and numerical study. Firstly, fourteen I-shaped aluminum alloy members were tested under eccentric compression at elevated temperatures. All the members failed by flexural-torsional buckling. The test results indicated that the bearing capacity of the specimens decreases with the rise of the temperature and the increase of the eccentricity. Subsequently, finite element (FE) models were established using the non-linear code ANSYS, and were verified against the experimental results. In order to develop a further understanding, numerical analysis was carried out using numerous FE models considering two kinds of aluminum alloy brands, two kinds of section types, nine types of section dimensions and three types of temperatures. Finally, 432 correlation curves were obtained and all of them were above the linear correlation curve. Due to its simplicity, the linear correlation curve was proposed to calculate the bearing capacity of aluminum alloy members under eccentric compression at temperatures under 300 ℃. The test data were used to validate the reliability of the proposed curve. The results revealed that the proposed correlation curve is safe and economical, while the design method suggested in EC9 is more conservative, which can be used as re-checking for important structures. Highlights: Aluminum alloy members were tested under eccentric compression in the heat. FE models of the specimens were established and verified against the test results. A linear correlation formula developed from Chinese code system was proposed. FE correlation curves and test points all laid above the proposed correlation line. The proposed correlation line is safe but more economical than Eurocode 9.